The Palgrave Handbook of International Political Theory
XX, 546 p. 2 illus.
Keywords: This is a major new work by internationally renowned editors and cutting edge contributors. The Handbook pulls off the difficult feat of simultaneously canonizing and de-parochializing International Political Theory, by extending its historical genealogy as well as its regional and thematic reach. The results are presented in accessible chapters for the student of the new field.“ - Peter Niesen, Professor of Political Theory, University of Hamburg, Germany “As the world confronts new challenges like pandemics and climate change, academic political theory has struggled to keep pace with events. Increasingly, our thinking must become international in scope. Focusing on themes from realism, sovereignty, and the nation-state to post-colonialism, gender, and indigeneity, these volumes attempt to bring political theory into the twenty-first century. The editors have brought together animpressive cast of contributors each of whom adds a distinctive voice to this chorus. This collection will provide an invaluable resource for scholars and students pondering the problems not only of today or tomorrow but of the future.” - Steven B. Smith, Alfred Cowles Professor of Political Science, Yale University, USA This handbook provides an exploration of the field of International Political Theory (IPT), which in its broadest terms, examines the ways in which ideas about justice, sovereignty, and legitimacy shape international politics. It is a comprehensive resource for those interested in understanding the philosophical, political, and legal issues that arise from interactions between states, peoples, and global actors. The two volumes of the handbook cover a wide range of topics, from the foundations of international political thought to the latest debates in the field. They are designed to give readers a comprehensive overview of the key concepts and arguments within international political theory and provide an introduction to the main debates in the field.Volume 1 takes us from the ancient world to the formation of the modern state system as we lay the groundwork for a critical understanding of changes in, and challenges to, core ideas such as sovereignty, international law and territorial integrity. The contributions to this volume explore the European domination of the discipline providing insights into how it came to conceive the world in its own image. They also focus on non-Western perspectives and reactions to European hegemony. Howard Williams is Distinguished Honorary Professor in the School of Law and Politics at Cardiff University, and Emeritus Professor of Political Theory in the Department of International Politics at Aberystwyth University, UK. David Boucher is Professor of Political Philosophy and International Relations at the University of Cardiff, UK, and Distinguished Visiting Professor at the University of Johannesburg (2015-25), South Africa. Peter Sutch is Professor of Political and International Theory at Cardiff University, UK. He is also Visiting Professor at the University of the Witwatersrand, South Africa. David Reidy is Professor of Philosophy at The University of Tennessee, USA. Alexandros Koutsoukis is Lecturer in International Relations at the University of Central Lancashire, UK. .